Comparing barriers and enablers of women's health leadership in India with East Africa and North AmericaResearch in context - Shagun Sabarwal; Jade Lamb; Shereen Bhan; Kerry Bruce; Gabrielle Plotkin; Christine Robinson; Norah Obudho; Amie Batson (Elsevier, 2023)
Summary: Background: Women are estimated to hold between 70 and 75% of global health positions worldwide yet persistent inequities in power and leadership remain. There is little information on specific enablers and barriers that women working in public health face in India and how those compare with other regions. Methods: We collected and analyzed information from women working in public health in India and East Africa (Kenya, Rwanda, and Uganda) and in global health (Canada and United States), to understand and document the specific enablers and barriers women face in India, compared with other regions. Findings: Several universal themes emerged around factors enabling (mentors, professional networks, leadership based in empathy and team building) or impeding (obvert bias and family responsibilities) women across all contexts. Within this, there are nuances in how women's leadership growth factors and obstacles play out in India differently than in other contexts. Interpretation: There are important similarities in the enablers and barriers faced by women in India and other geographies and important ways these differs in for women in India. By designing programs and policies at institutional levels to address these factors, we can create a professional ecosystem that works for women in health and beyond. Funding: This research was funded by WomenLift Health, which is funded by the Bill and Melinda Gates Foundation. Representatives from WomenLift Health, listed as authors, participated in the conceptualization of the research to define objectives and core questions, provided commentary and revision to improve the manuscript, and supervised the progress of the research.